Metode Efektif Mengajarkan Karakter Pada Anak Usia Dini - Eva Atitawati; Sandrina Ramadani; Ali Iskandar; Neela Afifah (Yayasan Cendekia Gagayunan Indonesia, 2025)
Character education in early childhood plays a crucial role in forming a personality with noble and responsible morals since the early development period. Early age is a golden period where moral and ethical values can be instilled effectively through an approach that is appropriate to the stages of child development. This study aims to examine effective methods in teaching character to early childhood. This study uses a descriptive qualitative method with a library research approach. Data were obtained through literature studies from books, journals, and relevant research reports. The analysis technique used is content analysis, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the exemplary, habituation, and storytelling methods are effective learning strategies in instilling character values in children. Exemplary provides concrete examples of positive behavior, habituation trains children in good habits consistently, and storytelling instills moral values through fun media. With the application of the right method, character education can take place optimally and naturally in early childhood.